KADERISASI PARTAI POLITIK DAN KESIAPANNYA MENGHADAPI PEMILIHAN UMUM KEPALA DAERAH TAHUN 2015: KASUS USUNGAN NON-KADER DPD PAN KABUPATEN MAJENE - Muhammad Muhammad (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2016)
One of the succesful indicator of political party to conduct the forming of cadres is by seeing its ability in preparing its cadresin every momentum of political dispute. In accordance with those matters, each political party certainly have characteristic itself in the lineof struggle and ideology in cases where just people who had passed the forming of cadres process that moreunderstandthe character of its political party. Therefore, it can be irony if there is political party who carry the candidate of district head that not derive from its cadres. Whereas, the ideology and the principle lineof struggle ideally become compulsory orientation for each political party toundergo its strategic role in political system.The focus is to identify the phenomenon of DPD PAN at Majene Regency who carrycandidate pair for regent and deputy of regent Rizal Sirajuddin-Mulyadi Bintaha that not derive from the cadres of PAN. Ironically, considering that PAN constitutesthe party by a majority chair in DPRD (Legislative Assembly at Regency)of Majene Regency all at once its cadres are the head of DPRD. That fact precisely describe PAN as the greatest partyin Majene that surely have proper infrastructure and very suitable if in General Election of the District Head jointly in Majene to carry its cadres itself. From the focus of this Problem, it will be arranged theoretical framework and the writer idea in looking at formulation till mechanism ofthe forming of cadresthatproperly be operated for political party. Moreover, at the process of political rectruitment to becarried in General Election of the District Head, it will be also reviewedthe expectation and itschallenge for political party.The aim is become alternativereferencein seeing the dynamic of political party at the local degree, especially khusunya kabupaten Majene. Accordingly, it become recomendation for political partyin order that the function of the forming of cadresand its political rectruitment canfare well properly for the sake of the process of ideal democracy consolidation in Indonesia.